Restructured Fish Nuggets from ‘Wallago Attu’ Extended with Soy Protein Isolate - Biswas, Olipriya; Das, Sudip Kumar; Biswas, S. (Journal of Meat Science, 2016)
The present study was conducted to prepare restructured fish nuggets from comparatively low-value cuts of ‘Wallago attu’ (Boal), with incorporation of soy protein isolate at different levels viz. 2.5% (T1), 5% (T2) and 7.5% (T3). Physicochemical, microbiological and sensory qualities were estimated on 0, 3, 7 and 14 days of refrigerated storage. Cooking yield (%) and Water Holding Capacity (WHC) were found to be significantly higher (p
Keywords: Fish; Wallago attu; Restructured; Nuggets; Soy protein